Flexible Artificial Synapses: Transferable and Flexible Artificial Memristive Synapse Based on WOx Schottky Junction on Arbitrary Substrates (Adv. Electron. Mater. 12/2018). (10th December 2018) - Lin, Ya; Zeng, Tao; Xu, Haiyang; Wang, Zhongqiang; Zhao, Xiaoning; Liu, Weizhen; Ma, Jiangang; Liu, Yichun
Abstract : Using a nondestructive water‐dissolution method, Haiyang Xu, Zhongqiang Wang, and co‐workers demonstrate a transferable WOx ‐based memristor with a NaCl substrate as the sacrificial layer in article number1800373 . The synaptic devices are transferred onto diverse substrates, presenting excellent flexibility and high mechanical endurance. The essential functions of synaptic plasticity are obtained by the device in the bent state. The work presents a feasible method that enables inorganic memristors for transferable applications.